Burkholderia pseudomallei and Burkholderia mallei vaccines: Are we close to clinical trials?. Issue 44 (20th October 2017) - Titball, Richard W.; Burtnick, Mary N.; Bancroft, Gregory J.; Brett, Paul
Abstract: B. pseudomallei is the cause of melioidosis, a serious an often fatal disease of humans and animals. The closely related bacterium B. mallei, which cases glanders, is considered to be a clonal derivative of B. pseudomallei . Both B. pseudomallei and B. mallei were evaluated by the United States and the former USSR as potential bioweapons. Much of the effort to devise biodefence vaccines in the past decade has been directed towards the identification and formulation of sub-unit vaccines which could protect against both melioidosis and glanders. A wide range of proteins and polysaccharides have been identified which protective immunity in mice. In this review we highlight the significant progress that has been made in developing glycoconjugates as sub-unit vaccines. We also consider some of the important the criteria for licensing, including the suitability of the "animal rule" for assessing vaccine efficacy, the protection required from a vaccine and the how correlates of protection will be identified. Vaccines developed for biodefence purposes could also be used in regions of the world where naturally occurring disease is endemic.